PENGARUH POST PURCHASE REMORSE TERHADAP NEGATIVE EMOTIONS, LEVEL OF SATISFACTION, EXTENT OF RUMINATION DAN BRAND SWITCHING (STUDI PADA KONSUMEN GENERASI Y PENGGUNA SMARTPHONE DI INDONESIA) - Baramadya; Purwanto; Mochamad Fatchurrohman (Media Mahardhika, 2023)
The purpose of this study was to determine the effect of post-purchase remorse on the level of satisfaction, the extent of rumination and brand switching, the effect of post-purchase remorse on negative emotions and level of satisfaction, the effect of post-purchase remorse on negative emotions and the extent of rumination. The population and sample in this study are all smartphone users in the millennial generation in Indonesia who have financial independence. By using the purposive sampling method, the number of samples in this study was 171 respondents. The analysis technique used is Structural Equation Modeling (SEM) using the Analysis of Moment Structures (AMOS) version 24.0 program. The results showed a significant influence between the variables of post-purchase remorse, level of satisfaction, negative emotions, extent of rumination, and brand switching. Insignificant influence occurs in the relationship of negative emotion variables to level of satisfaction and extent of rumination..